Made-to-Measure: In and Out of Touch with the Old-Growth Forest - Vola, Joonas; Rautio, Pasi; Rantala, Outi (Palgrave Macmillan, 2024)
The condition of forests is a major issue when it comes to climate change and biodiversity. One way to define the quality of a forest is by its age. In the cross pressure of socio-economic and ecological guidelines, what qualifies as an old-growth forest is not determined by a mere number but the co-constitution of various measurements, indicators, political ambitions, and the performance of the measured biological ‘units’ themselves. This transdisciplinary chapter studies how old-growth forests are made-to-measure, moving from close proximity encounters with an indicator organism, being-with-beard lichen, to the internationally defined level and timescale of economic activity and (un)management in categorising forest ecology, wherein various compromises in decision-making may also compromise local ecosystems and the vastness of scale in the biosphere. The study heads off to the ‘roots’ of science—definitions, conceptualisations, onto-epistemology, and methodologies—considering how they as active processes are performing the entity of the ‘old-growth forest’ by cutting-together-apart on multiple scales.